At Least One Cyclic Teriparatide Administration Can Be Helpful to Delay Initial Onset of a New Osteoporotic Vertebral Compression Fracture - Suk, Kyung Soo (Yonsei University College of Medicine, 2014)
PURPOSE: Teriparatide markedly increases bone formation and strength, while reducing the incidence of new-onset osteoporotic vertebral compression fractures (OVCFs). In some countries, expenses for teriparatide use are covered by medical insurance for up to 6 months; however, the national medical insurance of the authors' country does not cover these expenses. This retrospective cohort study compared the therapeutic effects of teriparatide on the initial onset of a new OVCF after treatment of osteoporosis and/or related OVCFs with regard to therapeutic durations of longer than 3 months (LT3M) or shorter than 3 months (ST3M). MATERIALS AND METHODS: From May 2007 to February 2012, 404 patients who were prescribed and administered teriparatide and who could be followed-up for longer than 12 months were enrolled. They were divided into two groups depending on teriparatide duration: LT3M (n=132) and ST3M (n=272). RESULTS: The group with the teriparatide duration of LT3M showed significantly less development of an initial OVCF within 1 year (p=0.004, chi-square). Duration of teriparatide use, body mass index, pre-teriparatide lowest spinal bone mineral density, and severity of osteoporosis significantly affected multiple regression analysis results (p<0.05). Survival analysis of first new-onset OVCFs demonstrated a significantly better survival rate for the LT3M group (log rank, p=0.005). Also, the ST3M group showed a higher odds ratio of 54.00 for development of an initial OVCF during follow-up than the LT3M group (Mantel-Haenzel common odds ratio, p=0.006). CONCLUSION: At least one cyclic teriparatide administration is recommended to provide a protective effect against the initial onset of a new OVCF for up to one year after therapy.